Paroxysmal Atrial Fibrillation Originating From the Inferior Vena Cava: A Case Report and Literature Review - Tao, Yirao; Yang, Donghui; Chen, Liang (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation is a common arrhythmia, but atrial fibrillation originating in the inferior vena cava is extremely rare. Here, we present a case of a 51-year-old woman with paroxysmal atrial fibrillation, who was admitted to our hospital for radiofrequency ablation. The atrial fibrillation persisted despite pulmonary vein isolation. The inferior vena cava was then identified not only as a trigger but also as the driver to maintain atrial fibrillation, and tachycardia terminated successfully by discharging at the inferior vena cava. Furthermore, we performed a literature review of five previous case reports on this subject.